NONNEUTRALITY OF MONEY IN DISPERSION: HUME REVISITED. (27th February 2019) - Jin, Gu; Zhu, Tao
Abstract: For a class of standard and widely used preferences, a one‐shot money injection in a standard matching model can induce a significant and persistent output response by dispersing the distribution of wealth. Decentralized trade matters for both persistence and significance. Following the injection, the price response may be sluggish, the markup may move up with output, and both the interest rate and the inflation rate may drop below their trend levels.